ENERGY AND PROTEIN AVAILABILITY WITH STUDENT FOODY ATRACTION LEVEL AT PONDOK TAHFIDZ DARUL QURAN JUNIOR HIGH SCHOOL, MOJOKERTO CITY - putri, sabrina (Jurnal Gizi dan Kesehatan Nusantara, 2024)
The common nutritional problems among teenagers are both undernutrition and overnutrition. Adequate intake of nutrients, especially energy and protein, is crucial for adolescents. Insufficient nutrient intake can have negative effects, such as lack of concentration during studying, impaired growth, decreased productivity, easy fatigue, susceptibility to illness, and impact on nutritional status.The nutritional status of students in the boarding school is influenced by food intake, nutrient availability, and food acceptance during the provision of dormitory meals.The objective of this study is to analyze the availability of energy and protein as well as the students’ food preferences at SMP Pondok Tahfidz Darul Quran in Mojokerto City. The research design is a quantitative descriptive study. The research sample was all female students at SMP Pondok Tahfidz Darul Quran with a total sample of 137 students using the total sampling method. The instrumens used were the Food weighing Form and the Preference Level Form. During the implementation of the food cycle with a 7-day menu, the average availability of energy was found to be 1016.55 kcal/person/day (42.35%). Similarly, the availability of protein was 49.82 g/person/day (79.08%). Among the most preferred menu options are crispy fried chicken, shredded chicken stir-fry, soto (Indonesian soup), meatballs, and chicken in soy sauce. On the other hand, the disliked menu options include pindang stew, stir-fried tofu with chicken liver, and stir-fried potatoes with boiled eggs and tofu. Keywords: Nutrition for teenagers, food availability, Preference Level, Nutritional Status, Body Mass Index